2015
DOI: 10.1016/j.mcn.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 in injured rat spinal cord: Implications for macrophage phagocytosis and neural repair

Abstract: Galectin (Gal)-1 is a small carbohydrate-binding protein and immune modulatory cytokine that is synthesized locally at the site of peripheral nerve injury. In this environment, Gal1 can promote regeneration of injured peripheral axons, in part by modifying the function of macrophages recruited to the site of injury. Unlike in injured peripheral nerves, macrophages do not promote axon regeneration in the injured central nervous system (CNS), perhaps because Gal1 levels are not regulated appropriately. Because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In this regard, the role of Gal1 in neurodegeneration following brain injury has been largely appreciated. It has been reported that Gal1 is involved in the regulation of astrocyte reactivity [59] and that this lectin is important for modulating phagocytosis, inflammation, gliosis and axon growth after spinal cord injury [60, 61]. Moreover, astrocyte-derived Gal1 has been proposed to play a role in neuromodulation and microglia polarization in a model of multiple sclerosis [24] and in axonal degeneration in a model of amyotrophic lateral sclerosis [62].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the role of Gal1 in neurodegeneration following brain injury has been largely appreciated. It has been reported that Gal1 is involved in the regulation of astrocyte reactivity [59] and that this lectin is important for modulating phagocytosis, inflammation, gliosis and axon growth after spinal cord injury [60, 61]. Moreover, astrocyte-derived Gal1 has been proposed to play a role in neuromodulation and microglia polarization in a model of multiple sclerosis [24] and in axonal degeneration in a model of amyotrophic lateral sclerosis [62].…”
Section: Discussionmentioning
confidence: 99%
“…The small glycoproteins galectin-1 and −3 have broad functions in many tissues. In SCI their function is currently unclear; galectin-1 is thought to be neuroprotective 43 and to modulate macrophage behavior in the injury epicentre 44 , while galectin-3 is likely associated with secondary inflammatory events 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to injury in non-CNS tissue successfully sterilizes, remodels, and repairs the wound within weeks [7,153]. In contrast, inflammation begins soon after SCI, and a disproportionate pro-inflammatory response persists into chronic phases [154][155][156][157][158] without appreciably enhancing tissue repair or functional recovery. Given that microglia/macrophages display phenotypic plasticity in time based on local conditions [159], it appears that the chronic SCI environment promotes and maintains exaggerated proinflammatory microglia/macrophage polarization.…”
Section: Activated Microglia (And Macrophages) Around the Lesion Secrmentioning
confidence: 99%